Economic Operation of a Micro-Grid considering Demand Side Flexibility and Common ESS Availability - Erenoglu, Ayse Kubra; Sengor, Ibrahim; Erdinc, Ozan; Tascikaraoglu, Akin; Catalao, Joao P. S. (IEEE, 2018)
The micro-grid concept has recently gained increasing attention for power system operators to increase the operational effectiveness and provide a more reliable, sustainable and economic power system. To ensure the autonomous power supply when disconnected from the bulk power system, energy storage system (ESS) options as well as demand side flexibility can be used to provide the local balance between time-varying production and consumption in a micro-grid structure. In this study, the demand side flexibility via thermostatically controllable appliances (TCAs)-based direct load control (DLC) strategies and common ESSs-based bi-directional energy flow possibility is considered for the economic operation of a micro-grid. Different case studies are conducted for validating the effectiveness of the proposed structure.
Keywords: Common energy storage system; demand side flexibility; economic operation; electric vehicle; micro-grids; STORAGE; MANAGEMENT; Engineering